Stability of refractive outcomes after hyperopic LASIK with and without Mitomycin C application: a randomized controlled trial - Amr Saad; Johannes Steinberg; Andreas Frings (Scientific Reports)
Abstract To assess the efficacy, safety, and stability of refractive outcomes in hyperopic Laser-Assisted in Situ Keratomileusis (LASIK) with and without the application of Mitomycin C (MMC). This randomized, parallel group, controlled multicenter trial included 140 hyperopic eyes. The participants were randomly assigned to two groups: one receiving LASIK with mitomycin C (MMC) (n = 70) and the other receiving LASIK without MMC (n = 70). The primary outcome measures were uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and safety parameters at six months postoperatively. The statistical analysis employed t-tests, Mann-Whitney tests, and Fisher’s Exact Test, with a significance level of p < 0.05. All 140 eyes (70 per group) were analyzed. No statistically significant differences were identified between the two groups in postoperative UDVA, CDVA, or safety parameters (p > 0.05). Both groups demonstrated highly effective and safe refractive outcomes. No intraoperative complications or postoperative adverse events were observed. Age and preoperative spherical equivalent did not significantly affect outcomes. Hyperopic LASIK with and without MMC showed comparable efficacy, safety, and stability of refractive outcomes at the six-month postoperative interval. Although MMC use in hyperopic LASIK appears to be a safe procedure, it was not found to be significantly superior to conventional LASIK. Further investigation with longer follow-up periods and larger cohorts is necessary to confirm these results.